The Viability of Online Education in India: Its Safety and Limitaions: Exploring the Viability and Challenges of Online Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The world is moving at a pace which is quite rapid. Especially after globalization, the movement has been rapid in a way that it has bought many technological advancements on its way. One such advancement is seen even in the field of education. The old classroom system has changed over the years and online education is currently the trend that is being popularized. Students going to school no more have to carry books and a lot of weight and rather prefer to carry a laptop or tablet which has all softwares. However, with everything being online, there are certain disadvantages which comes with them. The digital infrastructure also bring issues in relation with privacy. This research paper aims at covering all major concepts of e-learning at the first place. While explaining them in detail, the author also stressed on the disadvantages of it. The paper also is a good way to learn all about the new education policy with special emphasis on the digital policy. With more increase in the internet users, the limitations cannot be ignored. There are ways to avoid problems caused by internet and suggestions have been added in that regard.